2022
DOI: 10.1016/j.ijcard.2021.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Mannose as a biomarker of coronary artery disease: Angiographic evidence and clinical significance

Abstract: Background: High mannose has previously associated with insulin resistance and cardiovascular disease (CVD). Our objective is to establish whether mannose is associated with anatomical evidence of coronary artery disease (CAD). Methods: Plasma mannose concentrations were measured by liquid chromatography/tandem mass spectrometry in a discovery cohort (n = 513) and a validation cohort (n = 221) of carefully phenotyped individuals. In both cohorts CAD was quantitated using state-of-the-art imaging techniques (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Even though there is no reference range for mannose concentrations, mainly because of different assay methods, our findings in patients with known DM, 98.0 (79.4−120.7) μmol/L, are comparable to the concentrations measured by assays based on mass spectrometry [ 18 , 20 ]. Consistent with previous observations [ 9 , 12 , 20 , 21 ], we noted a positive linear correlation between mannose and glucose concentrations in the total population. Taken together, this strongly supports the hypothesis that mannose is a strong marker of insulin resistance [ 11 , 12 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Even though there is no reference range for mannose concentrations, mainly because of different assay methods, our findings in patients with known DM, 98.0 (79.4−120.7) μmol/L, are comparable to the concentrations measured by assays based on mass spectrometry [ 18 , 20 ]. Consistent with previous observations [ 9 , 12 , 20 , 21 ], we noted a positive linear correlation between mannose and glucose concentrations in the total population. Taken together, this strongly supports the hypothesis that mannose is a strong marker of insulin resistance [ 11 , 12 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…A large prospective cohort study reported an association between mannose levels and incident T2DM and CV outcomes including CHD and MI [ 9 ]. A validation study, including patients with varying CV risk whose CAD was quantitated by coronary computed angiography, invasive coronary angiography and optical coherence tomography, found an association between plasma mannose and CAD with a vulnerable plaque phenotype, which was independent of traditional CV risk factors [ 12 ]. In the effort to minimize the effect of additional confounders the present study selected patients with a first MI, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disorders of glucose metabolism will reduce angiogenesis and cardiac antioxidant capacity by affecting molecular signaling pathways, which ultimately lead to heart disease 20 . Studies showed ultramarathon runners had been detected high levels of d -mannose in their urine with the risk of myocardial ischemia 21 . d -mannose-1-phosphate easily reacts with proteins or lipids through the glycosylation process and generates glycosylation end products (AGEs) which easily cause myocardial lipid metabolism disorders, myocardial chronic inflammation, and cardiomyocyte apoptosis 19 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Mannose supplementation in chow-fed mice, however, did not have as pronounced of an effect on weight gain attenuation suggesting that mannose has a greater impact in pathological conditions. In addition, plasma levels of mannose have recently been shown to be a biomarker of CAD and a more vulnerable plaque phenotype 55 . It is not clear whether mannose is related to CAD because it marks insulin resistance or because of an intrinsic biological property 56 .…”
Section: Discussionmentioning
confidence: 99%